Why not, Lafayette? - Fritz, Jean.; Himler, Ronald (New York : G.P. Putnam's Sons, 1999)
Traces the life of the French nobleman who fought for democracy in revolutions in both the United States and France.
Includes bibliographical references (p. 81-82) and index.
Keywords: Lafayette, Marie Joseph Paul Yves Roch Gilbert Du Motier, -- marquis de, -- 1757-1834 -- Juvenile literature; Lafayette, Marie Joseph Paul Yves Roch Gilbert Du Motier, -- marquis de, -- 1757-1834.; United States. -- Army -- Biography -- Juvenile literature; Generals -- United States -- Biography -- Juvenile literature; Generals -- France -- Biography -- Juvenile literature; Generals; Statesmen; United States -- History -- Revolution, 1775-1783 -- Biography -- Juvenile literature